PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) BERBANTUAN MODUL SEKOLAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KOMPETENSI DASAR MENGGUNAKAN ALAT UKUR MEKANIK - Pribadi, Agung Rakhmat (Journal of Mechanical Engineering Learning, 2014)
The purpose of this action research is to increase the basic competence of learning result of the competence based using mechanical measuring devices through the application of Group Investigation (GI) learning modelÂ  assisted school modules, and to increase students learning activities. The reseach subject are students of SMK Muhammadiyah 1 Muntilan grade X TP4 year 2013/2014 with 37 students by using two cycles. Each siclus consist of 4 steps they are planning, action, observation, and reflection. The method of collecting data is using documentation, observation and test. The result of this research is there are increasement learning result of the students in basic competence using mechanical measuring devices. Based on the data analysis and content the result it self are, first, applying learning model of group investigation that helped by school module are able to increase the students learning result, it can be known from the students result of first cycle that are 61,4 become 79,3 and in second cycle with the result prosentation from first cycle that are 48,65% become 81,08% in second cycle. The second, increasing students activities from 64% in first cycle become 84% in second cycle. From this data collection method, it was known that the prosentation of the students result in basic competence by using mechanical measuring devices are 45,95% students result KKM, and that have no good result are 54,05%. After applyn the learning model GI that helped by using school module, the students learning result are increase in first cycle and second cycle , that are 48,65% in first cycle become 81,08% in second cycle. It means that the learning model type GI that helped by using school module in basic competence by using mechanical measuring devices are able to increase students learning result at SMK Muhammadiyah 1 Muntilan grade X TP4.